2021
DOI: 10.1093/icvts/ivab294
|View full text |Cite
|
Sign up to set email alerts
|

Subxiphoid-subcostal thoracoscopic thymectomy for seropositive myasthenia offers equivalent remission rates and potentially faster recovery

Abstract: OBJECTIVES To compare the perioperative and follow-up outcomes of patients with myasthenia gravis (MG) receiving subxiphoid-subcostal or unilateral thoracoscopic thymectomy and to identify the factors affecting MG prognosis. METHODS From January 2013 to December 2019, a total of 137 consecutive MG patients received subxiphoid-subcostal thoracoscopic thymectomy (STT, n = 65) or conventional unilateral thoracoscopic thymectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…After a 5-10 case learning curve, only patients with extensive invasion required conversion to an open sternotomy. The mean operative time in the subxiphoid group was 98 min, similar to other studies (13,18,21,22) with a range of 95-147 min. The blood loss in our study was 29.2 ml, which was also similar to their results, with a range of 25.5-73.8 ml.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…After a 5-10 case learning curve, only patients with extensive invasion required conversion to an open sternotomy. The mean operative time in the subxiphoid group was 98 min, similar to other studies (13,18,21,22) with a range of 95-147 min. The blood loss in our study was 29.2 ml, which was also similar to their results, with a range of 25.5-73.8 ml.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have confirmed the safety of the subxiphoid approach when applied to anterior mediastinal lesions ( 18 , 20 , 21 ). The approach via subxiphoid and subcostal arches was adopted in our center in 2017.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Carbon dioxide at 8 cmH 2 O pressure (1 cmH 2 O ¼ 0.098 kPa) was insufflated, and using the index finger as a guide, 5-mm puncture guides were inserted below the left and right rib margins as operative ports to establish the surgical system. [4][5][6][7] Both groups of patients underwent thymoma resection and lymph node dissection, which included resection of the thymoma and surrounding fat, lymph node dissection, and resection of invaded organs or tissues if necessary. In the subcostal thoracoscopy group, the surgery was performed using only a pair of grasping forceps and an ultrasonic scalpel.…”
Section: Surgical Positioning and Techniquesmentioning
confidence: 99%
“…Overall, 237 studies were searched from PubMed and Embase databases. After abstract/title screening and fulltext reading, 14 eligible studies were finally included in our meta-analysis according to the selection criteria (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%